STATUS KUALITAS PERAIRAN WADUK JUANDA - Yudhi Soetrisno (Jurnal Teknologi Lingkungan, 2003)
In attempt to know the trophic status and phytoplankton community in Juandareservoir this research was conducted. This research revealed that based onsecchi disk and concentration of Chlorophyll-a the Juanda reservoir have become eutrophic, with phytoplankton density was about 27,779-43,439 x 10-3 cell/l. The phytoplankton community was dominated by Synedra sp. (22.4-33.8%) and Microcystis sp. (10.2 –31.4 %;). However this result was about 1000 x bigger than previous publication which reported the phytoplankton density in Juanda reservoir was only about 621- 35,514 cell/l, and the phytoplankton community was dominated by Microcystis sp. which always > 85%. These differences were suggested due to using net-plankton in the sampling of phytoplankton.